Importance of Diffusion Weighted Magnetic Resonance Imaging in Evaluation of the Treatment Efficacy in Multiple Sclerosis Patients with Acute Attacks - Sahin, Tuna; Bozgeyik, Zulkuf; Menzilcioglu, Mehmet Sait; Citil, Serdal; Erbay, Mehmet Fatih (Int Scientific Information Inc, 2015)
Background: We planned to investigate contribution of DWMR to the treatment efficacy with ADC values which were measured in acute and chronic plaque before and after MS treatment. ADC changes in normal appearing white matter (NAWM) in patients with MS and healthy volunteers were also evaluated in this study. Material/Methods: 25 patients with MS and 30 healthy subjects with normal brain MR findings were included to our study. Contrast enhancement in plaque was evaluated as an acute, and non-contrast enhancement in plaque was evaluated as a chronic. Also, ADC measurements were performed using the same parameters in NAWM in plaque neighborhood and volunteers. Results were compared with appropriate statistical methods. Results: ADC values in acute and chronic plaques were decreased after the treatment, and these reductions were statistically significant for acute plaqus in b500 and for chronic plaques in b500 and b1000. The mean ADC values were measured as 1.53 +/- 0.49x10(-3) and 1.43 +/- 0.58x10(-3) in acute plaques and 1.40 +/- 0.35x10(-3) and 1.34 +/- 0.36x10(-3) mm(2)/sec in chronic plaques before and after the treatment. Conclusions: We think that DWMR have important role due to quantitative measurement ability in the evaluation of the treatment efficacy of the MS patients with acute attack in addition to contrast-enhanced MR sequence.
Keywords: Diabetes Mellitus, Type 2; Fatty Acid-Binding Proteins; PTEN Phosphohydrolase